(untitled) (International Journal of Physiotherapy, 2018)
Background: Mobile phone usage has become increasingly common in today’s youth. Its heavy use often leads to an addiction. Dependency on these devices could lead to postural dysfunctions as well as produce an adverse effect on psychology. Hence, this study is done to correlate mobile addiction with the craniovertebral angle, scapular index and Beck’s depression inventory score in young adults. Methods: An observational study was performed on 100 subjects out of which 51 were males and 49 were females in the age group of 18- 25 years who were pursuing their graduation and post-graduation courses. Mobile Phone Addiction Scale was used to determine the level of addiction. Craniovertebral angle, Scapular Index, and Beck’s Depression Inventory score were measured. Correlation of Mobile Phone Addiction Scale score with the above-mentioned parameters was done using GraphPad Instat Version 3.10 (Pearson correlation coefficient and Spearman correlation coefficient). Results: Mobile phone addiction was found low in 27%, moderate in 30% and high in 43% participants. There is significant correlation of mobile phone addiction scale score with Craniovertebral angle (r = -0.6470, p = <0.0001), Scapular Index (r = -0.4370, p = < 0.001) and Beck’s depression Inventory score (r = 0.3172, p = 0.0013). Conclusion: This study shows that mobile phone addiction is common amongst the youth and it contributes to considerable stresses on neck and shoulder. It could even cause unfavorable repercussion on an individual’s psychological status, such as depression. Hence, it is important to create awareness amongst the youth and take preventive measures for the same.